A method for preparing high conversion efficiency perovskite solar cell

By using organic salt passivator with strong UV absorption capacity to compensate for perovskite surface defects and provide water protection, the efficiency reduction of perovskite solar cells due to water and ultraviolet rays is solved, and its conversion efficiency and stability are significantly improved. .

CN119095405BActive Publication Date: 2025-01-10CHINA MINING RESOURCES (TIANJIN) NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411580325.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-10
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The efficiency of perovskite solar cells decreases due to their incompatibility with water and ultraviolet rays during normal operation, and the high density of surface defects during the preparation of solvent method limits its conversion efficiency and stability.

Method used

Using organic salts (4-(dimethylamino)-2-(trifluoromethoxy)phenyl)diphenyl(propyl)phosphonium bromide with strong UV absorption capacity as passivating agent to compensate for surface cation vacancies Defects and provides water vapor protection, perovskite solar cells are prepared by spin coating and annealing treatment.

Benefits of technology

The photoelectric conversion efficiency and stability of perovskite solar cells are significantly improved, and the tolerance to ultraviolet rays and water is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of perovskite solar cell preparation, and provides a method for preparing a high-conversion-efficiency perovskite solar cell, comprising the following steps: S100, preparing an electron transport layer; S200, preparing a TiO2 mesoporous layer; S300, preparing a passivator, wherein the passivator is (4-(dimethylamino)-2-(trifluoromethoxy)phenyl)diphenyl(propyl)phosphonium bromide; and then preparing a precursor solution; S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, and dripping an anti-solvent, and then annealing to obtain a perovskite solar cell. The present invention realizes a significant improvement in the photoelectric conversion efficiency of the perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite solar cell preparation, and in particular to a method for preparing a high-conversion-efficiency perovskite solar cell. Background Art

[0002] The extensive use of fossil fuels to generate electricity will cause serious damage to the environment, and photovoltaics, as a clean energy source, has attracted widespread attention from various industries. In recent years, through continuous improvements in film quality and preparation processes, the photoelectric conversion efficiency of perovskite solar cells has been greatly improved. In addition, due to the short preparation process cycle and low cost of perovskite solar cells, it has great potential for large-scale practical applications.

[0003] However, the high incompatibility of perovskite films with water and ultraviolet rays causes the efficiency of battery devices to slowly decrease during normal operation. At the same time, during the process of forming perovskite films by solvent method, a large number of ion defects will remain on the perovskite surface, which will induce irreversible degradation of the perovskite film and ultimately cause non-radiative recombination of carriers, severely limiting the conversion efficiency and stability of perovskite battery devices.

[0004] Since the defect density inside the perovskite crystal is much lower than the defect density on its surface, effectively passivating the surface defects can significantly improve the quality of the perovskite film. The cation vacancies on the surface of the perovskite crystal will lead to the random diffusion of halogen ions, causing the collapse of the surface skeleton structure. Adding the corresponding ion passivator on the surface can fill these vacant defects, effectively control the surface halogen ions, and achieve improved efficiency and stability of battery equipment.

[0005] In addition, perovskite films are easily degraded by ultraviolet rays, and water molecules can easily enter the crystal structure of perovskite and cause serious damage. Inorganic metal salts generally have strong water absorption, making it difficult to isolate perovskite from moisture and ultraviolet rays. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the related art. To this end, the present invention provides a method for preparing a high conversion efficiency perovskite solar cell, which can significantly improve the photoelectric conversion efficiency of the perovskite solar cell.

[0007] The present invention provides a method for preparing a high conversion efficiency perovskite solar cell, comprising the following steps:

[0008] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a first solvent to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate to obtain an electron transport layer;

[0009] S200, immersing the electron transport layer in a TiCl4 solution and performing a heating treatment; spin coating the mesoporous slurry on the surface of the electron transport layer after the heating treatment, and performing an annealing treatment to obtain a TiO2 mesoporous layer;

[0010] S300, dissolving CsI and RbI in a second solvent to obtain a second mixed solution; adding the second mixed solution, FAI, MABr and PbI2 into a third solvent to obtain a third mixed solution; dissolving a passivator in the third mixed solution to obtain a precursor solution; wherein the passivator is (4-(dimethylamino)-2-(trifluoromethoxy)phenyl)diphenyl(propyl)phosphonium bromide;

[0011] S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, adding an anti-solvent, and then annealing to obtain a perovskite solar cell.

[0012] According to a method for preparing a high conversion efficiency perovskite solar cell provided by the present invention, in the step S300, the method for preparing the passivating agent comprises the following steps:

[0013] Mixing 4-(diphenylphosphinoyl)-N,N-dimethyl-3-(trifluoromethoxy)aniline and bromopropane to obtain a mixture;

[0014] adding toluene to the mixture in a dry environment to obtain a reaction mixture;

[0015] The reaction mixture is heated, and the progress of the reaction is monitored by thin layer chromatography, and a reaction solution is obtained after the reaction is completed;

[0016] The reaction solution was distilled under reduced pressure to obtain a crude product, and the crude product was subjected to column chromatography to obtain a passivating agent.

[0017] According to a method for preparing a high conversion efficiency perovskite solar cell provided by the present invention, the amount of the brominated propane used is 1.0 equivalent to 2.0 equivalents of the 4-(diphenylphosphonyl)-N,N-dimethyl-3-(trifluoromethoxy)aniline.

[0018] According to a method for preparing a high conversion efficiency perovskite solar cell provided by the present invention, the heating temperature for heating the reaction mixture is 90° C. to 120° C.; the heating time is 4 hours to 20 hours;

[0019] The column chromatography treatment uses a mixture of ethyl acetate and n-hexane as an eluent, wherein the column chromatography treatment process includes:

[0020] The crude product was eluted with a mixture of ethyl acetate and n-hexane in a volume ratio of 20:1 as an eluent to obtain a first purified product;

[0021] The first purified product was eluted with a mixture of ethyl acetate and n-hexane in a volume ratio of 10:1 as an eluent to obtain a second purified product;

[0022] The second purified product was eluted with a mixture of ethyl acetate and n-hexane in a volume ratio of 5:1 as an eluent to obtain a passivating agent.

[0023] According to a method for preparing a high-conversion-efficiency perovskite solar cell provided by the present invention, the first solvent is at least one of 2-aminoethanol and 2-methoxyethanol.

[0024] According to a method for preparing a high conversion efficiency perovskite solar cell provided by the present invention, the mass ratio of the zinc acetate dihydrate to the magnesium acetate tetrahydrate is (3-5):1.

[0025] According to a method for preparing a high conversion efficiency perovskite solar cell provided by the present invention, in the step S100, the temperature of the annealing treatment is 300°C to 500°C.

[0026] According to a method for preparing a high conversion efficiency perovskite solar cell provided by the present invention, in the step S200, the concentration of the TiCl4 solution is 20 mmol / L, the heating temperature of the heating treatment is 50°C to 100°C, and the temperature of the annealing treatment is 300°C to 500°C;

[0027] The mesoporous slurry is prepared by uniformly dispersing Dyesol DSL18NR-T and isopropanol in a mass ratio of 1:10.

[0028] According to a method for preparing a high conversion efficiency perovskite solar cell provided by the present invention, in the step S300, the mass ratio of the CsI to the RbI is 1.2:1; the masses of the FAI, the MABr and the PbI2 are 3.6 times, 0.35 times and 9.4 times the mass of the RbI, respectively;

[0029] The second solvent is a polar solvent, the third solvent is a mixed solvent of DMF solvent and DMSO solvent, and the volume ratio of the DMF solvent to the DMSO solvent is 4:1.

[0030] According to a method for preparing a high conversion efficiency perovskite solar cell provided by the present invention, in the step S400, the anti-solvent is a non-polar solvent, and the temperature of the annealing treatment is 90° C. to 150° C.

[0031] The above one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects:

[0032] The method for preparing a high conversion efficiency perovskite solar cell provided by the present invention comprises the following steps:

[0033] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a first solvent to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate to obtain an electron transport layer;

[0034] S200, immersing the electron transport layer in a TiCl4 solution and performing a heating treatment; spin coating the mesoporous slurry on the surface of the electron transport layer after the heating treatment, and performing an annealing treatment to obtain a TiO2 mesoporous layer;

[0035] S300, dissolving CsI and RbI in a second solvent to obtain a second mixed solution; adding the second mixed solution, FAI, MABr and PbI2 into a third solvent to obtain a third mixed solution; dissolving a passivator in the third mixed solution to obtain a precursor solution; wherein the passivator is (4-(dimethylamino)-2-(trifluoromethoxy)phenyl)diphenyl(propyl)phosphonium bromide;

[0036] S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, and adding an anti-solvent, followed by annealing to obtain a perovskite solar cell; by using an organic salt (4-(dimethylamino)-2-(trifluoromethoxy)phenyl)diphenyl(propyl)phosphonium bromide) with strong ultraviolet absorption ability as a perovskite defect passivator, the ultraviolet rays are effectively prevented from damaging the perovskite film. At the same time, the cationic structure of the passivator itself compensates for the cationic vacancy defects left on the surface of the perovskite crystal during the solvent preparation process; and the hydrophobic groups of the passivator molecules can provide effective water vapor protection for the perovskite film. The passivator enables the modified perovskite solar cell device to achieve significant improvements in both photoelectric conversion efficiency and stability.

[0037] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The following embodiments are used to illustrate the present invention, but cannot be used to limit the scope of the present invention.

[0039] In the description of the embodiments of the present invention, it should be noted that the terms “first”, “second” and “third” are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0040] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0041] The following describes a method for preparing a high conversion efficiency perovskite solar cell according to the present invention, comprising the following steps:

[0042] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a first solvent to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate to obtain an electron transport layer.

[0043] In this embodiment, the first solvent is at least one of 2-aminoethanol and 2-methoxyethanol. The mass ratio of the zinc acetate dihydrate to the magnesium acetate tetrahydrate is (3-5):1, preferably 3.4:1. The annealing temperature is 300°C-500°C, preferably 500°C.

[0044] The preparation process of the transparent conductive glass substrate with fluorine-doped tin oxide is as follows:

[0045] The transparent conductive glass substrate with fluorine-doped tin oxide was immersed in acetone, deionized water and anhydrous ethanol, respectively, and cleaned in an ultrasonic cleaner for 15 minutes, and then sent to an ultraviolet light cleaner for 15 minutes to obtain a clean transparent conductive glass substrate with fluorine-doped tin oxide.

[0046] S200, immersing the electron transport layer in a TiCl4 solution and performing a heat treatment; spin coating the mesoporous slurry on the surface of the electron transport layer after the heat treatment, and performing an annealing treatment to obtain a TiO2 mesoporous layer.

[0047] Wherein, the concentration of TiCl4 solution is 20mmol / L, the heating temperature of the heating treatment is 50℃~100℃, preferably 70℃; the temperature of the annealing treatment is 300℃~500℃, preferably 500℃;

[0048] The mesoporous slurry is prepared by uniformly dispersing Dyesol DSL18NR-T and isopropanol in a mass ratio of 1:10.

[0049] S300, dissolving CsI and RbI in a second solvent to obtain a second mixed solution; adding the second mixed solution, FAI, MABr and PbI2 into a third solvent to obtain a third mixed solution; dissolving a passivating agent in the third mixed solution to obtain a precursor solution;

[0050] The passivator is (4-(dimethylamino)-2-(trifluoromethoxy)phenyl)diphenyl(propyl)phosphonium bromide. By using an organic salt (4-(dimethylamino)-2-(trifluoromethoxy)phenyl)diphenyl(propyl)phosphonium bromide with strong ultraviolet absorption ability as a perovskite defect passivator, ultraviolet rays are effectively prevented from damaging the perovskite film. At the same time, the cationic vacancy defects left on the surface of the perovskite crystal during the solvent preparation process are compensated by the cationic structure of the passivator itself. Moreover, the hydrophobic groups of the passivator molecules can provide effective water vapor protection for the perovskite film. The passivator enables the modified perovskite solar cell device to achieve significant improvements in photoelectric conversion efficiency and stability.

[0051] The mass ratio of the CsI to the RbI is 1.2:1; the masses of the FAI, the MABr and the PbI2 are 3.6 times, 0.35 times and 9.4 times the mass of the RbI, respectively;

[0052] The second solvent is a polar solvent, and in this embodiment, it is DMSO solvent. The third solvent is a mixed solvent of DMF solvent and DMSO solvent, and the volume ratio of the DMF solvent to the DMSO solvent is 4:1.

[0053] Furthermore, the preparation method of the passivating agent comprises the following steps:

[0054] 4-(diphenylphosphinoyl)-N,N-dimethyl-3-(trifluoromethoxy)aniline and bromopropane are mixed to obtain a mixture; the amount of bromopropane used is 1.0 to 2.0 equivalents of the 4-(diphenylphosphinoyl)-N,N-dimethyl-3-(trifluoromethoxy)aniline, preferably 1.2 equivalents.

[0055] In a dry environment, toluene is added to the mixture to obtain a reaction mixture; toluene is an aprotic solvent, which is beneficial to improving the reaction rate and selectivity;

[0056] The reaction mixture is heated at a temperature of 90° C. to 120° C., preferably 110° C. to 120° C.; the heating time is set to 4 hours to 20 hours, preferably 12 hours; the reaction progress is monitored by thin layer chromatography, and a reaction solution is obtained after the reaction is completed;

[0057] The reaction solution is distilled under reduced pressure to obtain a crude product, and the crude product is subjected to column chromatography to obtain a passivating agent. The column chromatography treatment uses a mixture of ethyl acetate and n-hexane as an eluent, and further, the column chromatography treatment process includes:

[0058] The crude product is eluted with a mixture of ethyl acetate and n-hexane in a volume ratio of 20:1 as an eluent to obtain a first purified product; most of the impurities in the crude product are eluted and dissolved in the eluent, thereby completing the removal of most of the impurities;

[0059] The first purified product is eluted with a mixture of ethyl acetate and n-hexane in a volume ratio of 10:1 as an eluent to obtain a second purified product; the remaining impurities in the first purified product are eluted and dissolved in the eluent to complete the removal of all impurities;

[0060] The second purified product is eluted with a mixture of ethyl acetate and n-hexane in a volume ratio of 5:1 as an eluent to obtain a passivating agent. That is, after the first two elutions, all the impurities attached to the chromatography column are eluted and removed, and the remaining second purified product attached to the chromatography column is the passivating agent. Through the third elution, the passivating agent is separated from the chromatography column and dissolved in a mixture of ethyl acetate and n-hexane in a volume ratio of 5:1, and then recrystallized to obtain the passivating agent.

[0061] S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, adding an anti-solvent, and then annealing to obtain a perovskite solar cell.

[0062] The anti-solvent is a non-polar solvent, which is chlorobenzene in this embodiment. The annealing temperature is 90°C to 150°C, preferably 120°C.

[0063] In order to test the photoelectric conversion efficiency and stability of perovskite solar cells, the Spiro-OMeTAD solution was spin-coated on the surface of the perovskite layer of the perovskite solar cell to test the photoelectric conversion efficiency of the perovskite solar cell. The P3HT solution was spin-coated on the surface of the perovskite layer of the perovskite solar cell to test the stability of the perovskite solar cell.

[0064] The Spiro-OMeTAD solution is a mixed solution consisting of a chlorobenzene solution of Spiro-OMeTAD, a tert-butylpyridine solution and an acetonitrile solution of Li-TFSI. The P3HT solution is prepared by dissolving P3HT in a chlorobenzene solution.

[0065] The performance characterization test benchmark of the perovskite solar cell prepared based on a method for preparing a high conversion efficiency perovskite solar cell in the present invention is:

[0066] A solar simulator (aperture 40 × 40 cm) equipped with a Keithley 2400 source meter and a 300 W collimated xenon lamp was used. 2 ) to test the volt-ampere characteristic curve of the solar cell device. Before the test, the light intensity needs to be calibrated to 100mW•cm under simulated AM1.5G light using a standard silicon solar cell. -2 .

[0067] The battery device efficiency test uses the FTO / Modified-ZnO / Meso-TiO2 / Perovskite / Spiro-OMeTAD / Au battery structure. The stability test uses the FTO / Modified-ZnO / Meso-TiO2 / Perovskite / P3HT / Au battery structure.

[0068] Example 1

[0069] A method for preparing a high conversion efficiency perovskite solar cell comprises the following steps:

[0070] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a mass ratio of 3:1 in 2-aminoethanol to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate at a temperature of 300° C. to obtain an electron transport layer.

[0071] S200, immersing the electron transport layer in a TiCl4 solution with a concentration of 20mmol / L and heating it at a temperature of 50°C; spin-coating the mesoporous slurry on the surface of the heated electron transport layer and annealing it at a temperature of 300°C to obtain a TiO2 mesoporous layer. The mesoporous slurry is prepared by uniformly dispersing Dyesol DSL18NR-T and isopropanol at a mass ratio of 1:10.

[0072] S300, adding 4-(diphenylphosphinoyl)-N,N-dimethyl-3-(trifluoromethoxy)aniline and bromopropane into a dry reactor, wherein the bromopropane is used in an amount of 1.0 equivalent of the 4-(diphenylphosphinoyl)-N,N-dimethyl-3-(trifluoromethoxy)aniline;

[0073] Toluene (as a reaction solvent) was added to the reactor, and the reactor was heated to 90° C. for 4 hours. The progress of the reaction was monitored by thin layer chromatography. When the reaction was completed, a reaction liquid was obtained. The reaction liquid was distilled under reduced pressure to obtain a crude product.

[0074] The crude product was eluted for the first time with a mixture of ethyl acetate and n-hexane in a volume ratio of 20:1 as an eluent to obtain a first purified product; the first purified product was eluted for a second time with a mixture of ethyl acetate and n-hexane in a volume ratio of 10:1 as an eluent to obtain a second purified product; the second purified product was eluted for a third time with a mixture of ethyl acetate and n-hexane in a volume ratio of 5:1 as an eluent to obtain a passivating agent.

[0075] CsI ​​and RbI in a mass ratio of 1.2:1 are dissolved in DMSO solvent to obtain a second mixed solution; the second mixed solution, FAI, MABr and PbI2 whose masses are 3.6 times, 0.35 times and 9.4 times the mass of the RbI, respectively, are added to a mixed solvent of DMF solvent and DMSO solvent to obtain a third mixed solution; 0.2% of a passivator relative to the molar number of PbI2 is dissolved in the third mixed solution to prepare a precursor solution; wherein the volume ratio of the DMF solvent to the DMSO solvent is 4:1.

[0076] S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, and dropping chlorobenzene, followed by annealing treatment at a temperature of 90° C., to obtain a perovskite solar cell.

[0077] Example 2

[0078] A method for preparing a high conversion efficiency perovskite solar cell comprises the following steps:

[0079] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a mass ratio of 3.4:1 in 2-methoxyethanol to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate at a temperature of 500° C. to obtain an electron transport layer.

[0080] S200, immersing the electron transport layer in a TiCl4 solution with a concentration of 20 mmol / L, and heating it at a temperature of 70°C; spin-coating the mesoporous slurry on the surface of the electron transport layer after the heating treatment, and annealing it at a temperature of 500°C to obtain a TiO2 mesoporous layer.

[0081] The mesoporous slurry is prepared by uniformly dispersing Dyesol DSL18NR-T and isopropanol in a mass ratio of 1:10.

[0082] S300, adding 4-(diphenylphosphinoyl)-N,N-dimethyl-3-(trifluoromethoxy)aniline and bromopropane into a dry reactor, wherein the bromopropane is used in an amount of 1.2 equivalents of the 4-(diphenylphosphinoyl)-N,N-dimethyl-3-(trifluoromethoxy)aniline;

[0083] Toluene (as a reaction solvent) was added to the reactor, and the reactor was heated to 110° C. for 12 hours. The progress of the reaction was monitored by thin layer chromatography, and a reaction liquid was obtained after the reaction was completed. The reaction liquid was distilled under reduced pressure to obtain a crude product.

[0084] The crude product was eluted for the first time with a mixture of ethyl acetate and n-hexane in a volume ratio of 20:1 as an eluent to obtain a first purified product; the first purified product was eluted for a second time with a mixture of ethyl acetate and n-hexane in a volume ratio of 10:1 as an eluent to obtain a second purified product; the second purified product was eluted for a third time with a mixture of ethyl acetate and n-hexane in a volume ratio of 5:1 as an eluent to obtain a passivating agent.

[0085] CsI ​​and RbI in a mass ratio of 1.2:1 are dissolved in DMSO solvent to obtain a second mixed solution; the second mixed solution, FAI, MABr and PbI2 whose masses are 3.6 times, 0.35 times and 9.4 times the mass of the RbI, respectively, are added to a third solvent to obtain a third mixed solution; 0.3% of a passivator relative to the molar number of PbI2 is dissolved in the third mixed solution to obtain a precursor solution; wherein the third solvent is a mixed solvent of DMF solvent and DMSO solvent, and the volume ratio of the DMF solvent to the DMSO solvent is 4:1.

[0086] S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, and dropping chlorobenzene, followed by annealing treatment at a temperature of 120° C., to obtain a perovskite solar cell.

[0087] Example 3

[0088] A method for preparing a high conversion efficiency perovskite solar cell comprises the following steps:

[0089] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a ratio of 5:1 in a first solvent to obtain a first mixed solution; the first solvent is a mixed solvent of 2-aminoethanol and 2-methoxyethanol. Spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate at a temperature of 400° C. to obtain an electron transport layer.

[0090] S200, immersing the electron transport layer in a TiCl4 solution with a concentration of 20 mmol / L, and heating it at a temperature of 100°C; spin-coating the mesoporous slurry on the surface of the electron transport layer after the heating treatment, and annealing it at a temperature of 400°C to obtain a TiO2 mesoporous layer. The mesoporous slurry is prepared by uniformly dispersing Dyesol DSL18NR-T and isopropanol at a mass ratio of 1:10.

[0091] S300, adding 4-(diphenylphosphinoyl)-N,N-dimethyl-3-(trifluoromethoxy)aniline and bromopropane into a dry reactor, wherein the bromopropane is used in an amount of 2.0 equivalents of the 4-(diphenylphosphinoyl)-N,N-dimethyl-3-(trifluoromethoxy)aniline;

[0092] Toluene (as a reaction solvent) was added to the reactor, and the reactor was heated to 120° C. for 20 hours. The progress of the reaction was monitored by thin layer chromatography, and a reaction liquid was obtained after the reaction was completed; the reaction liquid was distilled under reduced pressure to obtain a crude product;

[0093] The crude product was eluted for the first time with a mixture of ethyl acetate and n-hexane in a volume ratio of 20:1 as an eluent to obtain a first purified product; the first purified product was eluted for a second time with a mixture of ethyl acetate and n-hexane in a volume ratio of 10:1 as an eluent to obtain a second purified product; the second purified product was eluted for a third time with a mixture of ethyl acetate and n-hexane in a volume ratio of 5:1 as an eluent to obtain a passivating agent.

[0094] CsI ​​and RbI in a mass ratio of 1.2:1 are dissolved in DMSO solvent to obtain a second mixed solution; the second mixed solution, FAI, MABr and PbI2 whose masses are 3.6 times, 0.35 times and 9.4 times the mass of the RbI, respectively, are added to a third solvent to obtain a third mixed solution; 0.4% of a passivator relative to the molar number of PbI2 is dissolved in the third mixed solution to obtain a precursor solution; wherein the third solvent is a mixed solvent of DMF solvent and DMSO solvent, and the volume ratio of the DMF solvent to the DMSO solvent is 4:1.

[0095] S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, and dropping chlorobenzene, followed by annealing treatment at a temperature of 150° C., to obtain a perovskite solar cell.

[0096] Comparative Example

[0097] The transparent conductive glass substrate with fluorine-doped tin oxide (FTO) was immersed in acetone, deionized water and anhydrous ethanol respectively and cleaned in an ultrasonic cleaner for 15 minutes, and finally sent to an ultraviolet light cleaner for 15 minutes to obtain a clean substrate for use.

[0098] Preparation of electron transport layer: Dissolve zinc acetate dihydrate (220 mg) and magnesium acetate tetrahydrate (64 mg) in a mixed solvent of 2-aminoethanol (80 μL) and 2-methoxyethanol (3.3 mL). Spin-coat the prepared precursor solution on the FTO substrate (rotation speed 3300 rpm, time 30 s), anneal the spin-coated glass substrate at 500 ° C for 30 min, and then cool to room temperature.

[0099] Preparation of TiO2 mesoporous layer: The prepared substrate was immersed in a TiCl4 solution (20 mM) and heated at 70 °C for 12 min. Then, the prepared mesoporous slurry (Dyesol DSL18NR-T and isopropanol were evenly dispersed in a mass ratio of 1:10) was spin-coated on the electron transport layer substrate at a speed of 5000 rpm for 40 s. Then, the substrate was annealed at 500 °C for 30 min and then cooled to room temperature.

[0100] Preparation of perovskite layer: CsI (77.94 mg) and RbI (63.7 mg) were dissolved in 200 μL of DMSO, and FAI (217 mg), MABr (29 mg), PbI2 (778.7 mg) and the above-prepared CsI / DMSO (62 μL) and RbI / DMSO (61 μL) were dissolved in a mixed solvent of DMF (970 μL) and DMSO (240 μL). The above-prepared perovskite precursor solution was first rotated at a speed of 1000 rpm for 15 seconds, and then rotated at a speed of 4000 rpm for 30 seconds to complete the spin coating of the perovskite precursor solution on the substrate. In the last 5 seconds of the spin coating process, 400 μL of chlorobenzene (as anti-solvent) was quickly added, and then placed on a hot plate for annealing at 150°C for 30 minutes to form a black film.

[0101] Preparation of hole transport layer: Spiro-OMeTAD: Dissolve Spiro-OMeTAD (100 mg) in 1 mL of chlorobenzene and add 24.5 μL of Li-TFSI / acetonitrile (520 mg / mL) and 40.3 μL of tBP. Spin coat the prepared solution on the surface of the perovskite film at 4500 rpm for 30 s. When testing stability, P3HT will be used as the hole transport layer. Dissolve 15 mg of P3HT in 1 mL of chlorobenzene and spin coat the prepared solution on the surface of the perovskite film at 4500 rpm for 25 s.

[0102] Deposition of metal electrodes: Use vacuum evaporation equipment to evaporate Au or Ag onto the surface of the hole transport layer under high vacuum to deposit a metal electrode with a thickness of 50 nm to obtain a perovskite solar cell.

[0103] Demonstration test of enhanced photoelectric capability

[0104] In AM1.5G 100mW•cm -2 Example 1, Example 2, Example 3 and the comparative example (active area of ​​0.04 cm 2 ), the battery efficiencies corresponding to Example 1, Example 2, and Example 3 are significantly improved relative to the comparative example, wherein the conversion efficiency of Example 1 is the highest at 21.58%, the conversion efficiency of Example 2 is the best, up to 21.96%, the conversion efficiency of Example 3 is the highest at 21.61%, and the conversion efficiency of the comparative example is the highest at 21.39%. It can be seen that the conversion efficiencies of Example 1, Example 2, and Example 3 are significantly higher than those of the comparative example.

[0105] Enhanced performance testing of water stability

[0106] Example 1, Example 2, Example 3 and the comparative example were placed in an environment with 65% humidity at room temperature. After 3000 hours, Example 2 still maintained an initial efficiency of more than 90%, and the initial efficiency of the comparative example was significantly worse than that of Example 1, Example 2 and Example 3, indicating that the water stability of the perovskite solar cell prepared in the embodiment of the present invention is significantly improved. The test results are shown in Table 1.

[0107] Table 1 Water stability test results

[0108]

[0109] Enhanced photostability testing

[0110] After placing Example 1, Example 2, Example 3 and the comparative example in a nitrogen environment and continuously irradiating Example 1, Example 2, Example 3 and the comparative example with an ultraviolet lamp for 1100 hours, Example 1, Example 2 and Example 3 can still maintain good initial efficiency (more than 80%), while the initial efficiency of the comparative example is severely attenuated. The test results are shown in Table 2.

[0111] Table 2 UV stability test

[0112]

[0113] Furthermore, the light stability of Example 1, Example 2, Example 3 and the comparative example was tested under the above conditions. After 1250 hours of simulated sunlight irradiation, Example 2 and Example 3 still maintained an initial efficiency of more than 85%, while the initial efficiency of the comparative example was only 59.2%, confirming the improvement of the light stability of the perovskite solar cells used in the embodiments of the present invention. The test results are shown in Table 3.

[0114] Table 3 Simulated sunlight stability test

[0115]

[0116] The above one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects:

[0117] The method for preparing a high conversion efficiency perovskite solar cell provided by the present invention comprises the following steps:

[0118] S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a first solvent to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; annealing the spin-coated substrate to obtain an electron transport layer;

[0119] S200, immersing the electron transport layer in a TiCl4 solution and performing a heating treatment; spin coating the mesoporous slurry on the surface of the electron transport layer after the heating treatment, and performing an annealing treatment to obtain a TiO2 mesoporous layer;

[0120] S300, dissolving CsI and RbI in a second solvent to obtain a second mixed solution; adding the second mixed solution, FAI, MABr and PbI2 into a third solvent to obtain a third mixed solution; dissolving a passivator in the third mixed solution to obtain a precursor solution; wherein the passivator is (4-(dimethylamino)-2-(trifluoromethoxy)phenyl)diphenyl(propyl)phosphonium bromide;

[0121] S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, and adding an anti-solvent, followed by annealing to obtain a perovskite solar cell; by using an organic salt (4-(dimethylamino)-2-(trifluoromethoxy)phenyl)diphenyl(propyl)phosphonium bromide) with strong ultraviolet absorption ability as a perovskite defect passivator, the ultraviolet rays are effectively prevented from damaging the perovskite film. At the same time, the cationic structure of the passivator itself compensates for the cationic vacancy defects left on the surface of the perovskite crystal during the solvent preparation process; and the hydrophobic groups of the passivator molecules can provide effective water vapor protection for the perovskite film. The passivator enables the modified perovskite solar cell device to achieve significant improvements in both photoelectric conversion efficiency and stability.

[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high conversion efficiency perovskite solar cell, characterized in that: The steps include: S100, dissolving zinc acetate dihydrate and magnesium acetate tetrahydrate in a first solvent to obtain a first mixed solution; spin-coating the first mixed solution on a transparent conductive glass substrate with fluorine-doped tin oxide to obtain a spin-coated substrate; Annealing the spin-coated substrate to obtain an electron transport layer; S200, immersing the electron transport layer in a TiCl4 solution and performing a heating treatment; spin coating the mesoporous slurry on the surface of the electron transport layer after the heating treatment, and performing an annealing treatment to obtain a TiO2 mesoporous layer; S300, dissolving CsI and RbI in a second solvent to obtain a second mixed solution; The second mixed solution, FAI, MABr and PbI2 are added to a third solvent to obtain a third mixed solution; a passivator is dissolved in the third mixed solution to obtain a precursor solution; wherein the passivator is (4-(dimethylamino)-2-(trifluoromethoxy)phenyl)diphenyl(propyl)phosphonium bromide; S400, spin-coating the precursor solution on the surface of the TiO2 mesoporous layer, adding an anti-solvent, and then annealing to obtain a perovskite solar cell.

2. The method for preparing a high conversion efficiency perovskite solar cell according to claim 1, characterized in that: In the step S300, the method for preparing the passivating agent comprises the following steps: Mixing 4-(diphenylphosphinoyl)-N,N-dimethyl-3-(trifluoromethoxy)aniline and bromopropane to obtain a mixture; adding toluene to the mixture in a dry environment to obtain a reaction mixture; The reaction mixture is heated, and the progress of the reaction is monitored by thin layer chromatography, and a reaction solution is obtained after the reaction is completed; The reaction solution was distilled under reduced pressure to obtain a crude product, and the crude product was subjected to column chromatography to obtain a passivating agent.

3. The method for preparing a high conversion efficiency perovskite solar cell according to claim 2, characterized in that: The amount of the bromopropane used is 1.0 to 2.0 equivalents of the 4-(diphenylphosphinoyl)-N,N-dimethyl-3-(trifluoromethoxy)aniline.

4. The method for preparing a high conversion efficiency perovskite solar cell according to claim 2, characterized in that: The reaction mixture is heated at a temperature of 90° C. to 120° C. and a heating time of 4 to 20 hours; The column chromatography treatment uses a mixture of ethyl acetate and n-hexane as an eluent, wherein the column chromatography treatment process includes: The crude product was eluted with a mixture of ethyl acetate and n-hexane in a volume ratio of 20:1 as an eluent to obtain a first purified product; The first purified product was eluted with a mixture of ethyl acetate and n-hexane in a volume ratio of 10:1 as an eluent to obtain a second purified product; The second purified product was eluted with a mixture of ethyl acetate and n-hexane in a volume ratio of 5:1 as an eluent to obtain a passivating agent.

5. The method for preparing a high conversion efficiency perovskite solar cell according to claim 1, characterized in that: The first solvent is at least one of 2-aminoethanol and 2-methoxyethanol.

6. The method for preparing a high conversion efficiency perovskite solar cell according to claim 1, characterized in that: The mass ratio of the zinc acetate dihydrate to the magnesium acetate tetrahydrate is (3-5):

1.

7. The method for preparing a high conversion efficiency perovskite solar cell according to claim 1, characterized in that: In the step S100, the temperature of the annealing treatment is 300°C to 500°C.

8. The method for preparing a high conversion efficiency perovskite solar cell according to claim 1, characterized in that: In the step S200, the concentration of the TiCl4 solution is 20 mmol / L, the heating temperature of the heating treatment is 50°C to 100°C, and the temperature of the annealing treatment is 300°C to 500°C; The mesoporous slurry is prepared by uniformly dispersing Dyesol DSL18NR-T and isopropanol in a mass ratio of 1:

10.

9. The method for preparing a high conversion efficiency perovskite solar cell according to claim 1, characterized in that: In the step S300, the mass ratio of the CsI to the RbI is 1.2:1; the masses of the FAI, the MABr and the PbI2 are 3.6 times, 0.35 times and 9.4 times the mass of the RbI, respectively; The second solvent is a polar solvent, the third solvent is a mixed solvent of DMF solvent and DMSO solvent, and the volume ratio of the DMF solvent to the DMSO solvent is 4:

1.

10. The method for preparing a high conversion efficiency perovskite solar cell according to claim 1, characterized in that: In the step S400, the anti-solvent is a non-polar solvent, and the temperature of the annealing treatment is 90°C to 150°C.

Citation Information

Patent Citations

  • Perovskite solar cell based on 3, 4, 9, 10-perylene tetracarboxylic dianhydride modification and manufacturing method

    CN110676388A

  • Perovskite solar cell based on double passivation layers and preparation method thereof

    CN117440738A